A patient's guide to medical imaging - Eisenberg, Ronald L.; Margulis, Alexander R. (Oxford University Press, 2011)
Medical imaging now plays a major role in diagnosis, choice of therapy, and follow-up. However, patients are often intimidated by the multiple imaging modalities available, the indications for their use, the imposing equipment, what the examinations are like and how long they last, and the advantages and disadvantages of various procedures. This book is designed to provide explanations for these and other issues in order to relieve some of the anxiety related to medical imaging studies